1991
DOI: 10.3109/10425179109020781
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of a functional member of the Em gene family from wheat

Abstract: We report the complete sequence of one functional member of the Em gene family whose expression in wheat embryos is regulated by a complex set of environmental and developmental controls, including the phytohormone abscisic acid (ABA). The Em coding region contains one short intron, and there is an inverted repeat in the transcribed 3'-flanking region. A 646 bp fragment from the 5' promoter, which was previously shown to direct ABA-regulated expression in transformed tobacco tissue and rice cells, is character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…Fifty-five bases upstream of the transcription start site is a CAT box consensus sequence for transcriprional initiation (Joshi, 1987). The presence of a CAT box in the emb-1 gene contrasts with the DCS gene of carrot (Franz et al, 1989) and at least one Em gene of wheat (Litts et al, 1991); both of these genes are expressed during embryo development but lack a clearly recognizable CAT box sequence. The DNA sequence 5' of the transcription unit has several repeated motifs that may have a role in regulation of transcription (see legend to Fig.…”
Section: Structure Of the Emb-1 Gene And Analysis Of The Transcriptiomentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-five bases upstream of the transcription start site is a CAT box consensus sequence for transcriprional initiation (Joshi, 1987). The presence of a CAT box in the emb-1 gene contrasts with the DCS gene of carrot (Franz et al, 1989) and at least one Em gene of wheat (Litts et al, 1991); both of these genes are expressed during embryo development but lack a clearly recognizable CAT box sequence. The DNA sequence 5' of the transcription unit has several repeated motifs that may have a role in regulation of transcription (see legend to Fig.…”
Section: Structure Of the Emb-1 Gene And Analysis Of The Transcriptiomentioning
confidence: 99%
“…Two long inverted repeats in the intron and in the 3'-untranslated sequence are underlined and underscored by >>>>>> (<<<<<<for the inverted sequence). Repeated motifs 5' of the transcription start site are underlined and indicated as follows: *Ca/cTACGTC, a portion of the putative ABA-response element and including the ACCT motif implicated in the regulation of expression of a wide number of other genes (Dwarki et ai., 1990;Guiltinan et al, 1990;Mundy et al, 1990;Schindler and Cashmore, 1990); "*GTCAATC, a motif associated with embryo-specific expression of P-conglycinin (Chen et al, 1988) and present in plant genes including Lea D19 and Em (Baker et al, 1988;Litts et al, 1991).…”
Section: ~G T T a C T G G A A T A A C T A~a C T T A T A C ' R G G T Tmentioning
confidence: 99%
“…Marcotte et al (1989) also observed that as the Em promoter fragment decreased from 554 to -168, there was a proportional decrease in the total GUS activity in both + and -ABA treatments, indicating that non-specific transcriptional enhancer sequences may also be represented in this region. This region is characterized by three stretches of 40-70 nucleotides each of which contains at least 84 % A or Ts (Litts et al, 1990). A/T-rich tracts have also been observed in several other 5' flanking regions of plant genes (Datta & Cashmore, 1989) and have been shown to enhance gene expression in chimeric genes in transgenic tobacco (Bustos et al, 1989).…”
Section: Regulation Of Aba-responsive Genesmentioning
confidence: 99%
“…The high conservation in all regions of the Group 1 LEA proteins and the presence of multiple tandem copies of the 20-amino acid motif clearly suggest an essential structural function (2). The single intron is in the same position in Lea4, LeaA2, a wheat Em gene (9), and the barley B19 genes (K.S. Jakobsen, personal communication (10) and the inversecomplement of the wheat Em ABRE element (6).…”
mentioning
confidence: 99%
“…The amino acid sequence of cDNA D19 is peculiar in having a carboxyterminal extension of 18 amino acids not found in its homologs (2), but the upstream region ofthe Lea4 gene does contain elements similar to those defined in a wheat Em gene (6), the only other group 1 Lea gene sequenced (9). To confirm the peculiar carboxy extension and to help define the developmental and environmental responsive regions in the cotton Lea4 gene, both alloalleles of cotton Lea4 and 10 Lea4 cDNAs were sequenced.…”
mentioning
confidence: 99%